Att utmana eller återskapa traditionen - Hans Larsson; Claes Nilholm (Educare)
Being part of a decentralized system Swedish schools have a rather large possibility to shape their own activities. In the present article we analyze the activities of different schools, working with children who are considered to have problems relating to others. Four schools represent a traditional way to work with these children. In contrast, two additional schools present challenges towards this tradition. Specifically, the work of these two latter schools is focused. The analysis is built upon interviews with three persons in each school: the headmaster, one teacher and the special educational needs coordinator (the SENCO). The two groups of schools are compared with regard to a number of themes: organizational solutions, the importance of school leadership, the role of the “small group”, the role of the SENCOs, occupational development, preventive work, and relations. The two groups of schools differ with regard to all these themes. Finally we discuss the implications of the two different approaches.